RESEARCH ON SINGLE-LEAF WALLS MADE WITH LIGHTENED CLAY BRICKS (Journal of Engineering Studies and Research, 2016)
This paper explains the studies conducted on the subject by RADEB (Research and Development in Energy and Buildings) Research Group at the University of La Rioja. The aim of this work is to study the possibility of improving the thermal transmittance of a single-leaf wall made with lightened clay bricks. A first aspect is to study the possibility of lightening the clay by using additives, reducing the clay’s conductivity without decreasing its resistive ability. The internal and external geometry of the bricks has been studied by the Finite Element Method (FEM). Different wall assemblies with these bricks have been studied.
Keywords: lightened clay brick; thermal transmittance; single-leaf walls; energy efficiency